Pengaruh Jangka Pendek Dan Jangka Panjang Variabel Makro Ekonomi Terhadap Ihsg Di Bursa Efek Indonesia Dengan Pendekatan Error Correction Model (ECM) - Ranto, Suryo Refli (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractThis study aims to empirically examine the effect of short-term and long-term Inflation, Amount of Current Money, Exchange Rate, Interest Rate of Bank Indonesia, World Oil Price (WTI) and Net Exports on the Composite Stock Price Index (IHSG) using the Error Correction Model method ( ECM) which is processed with reviews 6.0. During the observation period of 2000-2012, there was a relationship between macro variables and the movement of the JCI on the Indonesia Stock Exchange (IDX). The ECM test results show that inflation, exchange rates, and world oil prices have a significant effect on the JCI in the short term while the long-term variables that significantly affect the JCI are CPI, exchange rates, net exports, and world oil prices.Keywords: CSPI, CPI, JUB, Exchange Rate, Bank Indonesia Interest Rate (rSBI), World Oil Price (WTI), Net Export and Error Correction Model (ECM)